2021
DOI: 10.1007/s42452-021-04648-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly fluorescent CsPbBr3/TiO2 core/shell perovskite nanocrystals with excellent stability

Abstract: The poor stability of CsPbX3 (X = Cl, Br, I) perovskite nanocrystals is the most impediment to its application in the field of photoelectrics. In this work, monodisperse CsPbBr3/TiO2 nanocrystals are successfully prepared by coating titanium precursor on the surface of colloidal CsPbBr3 nanocrystals at room temperature. The CsPbBr3/TiO2 nanocomposites exhibit excellent stability, remaining the identical particle size (9.2 nm), crystal structures and optical properties. Time-resolved photoluminescence decay sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Additionally, their unsuitability for large-scale industrial synthesis requirements is another setback. To circumvent these challenges, several approaches have been proposed, such as encapsulation in inorganic shells, including ZnS, 8 CdS, 9 TiO 2 , 10 Al 2 O 3 , 11 PbSO 4 , 12 and mesoporous silica, 13 and embedding in polymer 14 and glass 15 matrices as well as heteroepitaxial structures, including CsPbBr 3 /Cs 4 PbBr 6 16 and CsPbBr 3 /CsPb 2 Br 5 core/shell structures. 17 Nevertheless, since these integration and incorporation methods are expensive, labor-intensive, and complex, they can only be performed in the laboratory and are difficult for synthesis and optimization for large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their unsuitability for large-scale industrial synthesis requirements is another setback. To circumvent these challenges, several approaches have been proposed, such as encapsulation in inorganic shells, including ZnS, 8 CdS, 9 TiO 2 , 10 Al 2 O 3 , 11 PbSO 4 , 12 and mesoporous silica, 13 and embedding in polymer 14 and glass 15 matrices as well as heteroepitaxial structures, including CsPbBr 3 /Cs 4 PbBr 6 16 and CsPbBr 3 /CsPb 2 Br 5 core/shell structures. 17 Nevertheless, since these integration and incorporation methods are expensive, labor-intensive, and complex, they can only be performed in the laboratory and are difficult for synthesis and optimization for large-scale production.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the absorption region < 400 nm was strong because of amorphous TiO 2 and carbon residues aer TiO 2 coating. 12 The X-ray diffraction (XRD) patterns of the CsPbBr 3 QDs and CsPbBr 3 /TiO 2 are shown in Fig. 2(m).…”
Section: Materials Characterizationmentioning
confidence: 99%
“… 10 H. Chen et al demonstrated a long lifetime of CsPbBr 3 /TiO 2 nanocrystals of about 4.04 ns of photoluminescence, and it remains stable after a period of two months in air. 12 Among different phases of TiO 2 , the anatase phase of TiO 2 demonstrates higher electron extraction properties, providing an efficient pathway to transport excited electrons from QDs. Furthermore, TiO 2 can protect QDs from degradation from external factors, which is crucial for developing optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al. reported the preparation of monodisperse CsPbBr 3 /TiO 2 core-shell NCs by coating titanium precursor on the surface of colloidal CsPbBr 3 NCs at room temperature ( Chen et al., 2021 ). The CsPbBr 3 /TiO 2 nanocomposites exhibit excellent stability, remaining identical particle size, crystal structures, and optical properties.…”
Section: Surface Engineeringmentioning
confidence: 99%